Solar energetic particle events related to disk-centre full-halo coronal mass ejections - Valtonen E.; Ameri D. (Italy, 2022)
We have investigated the occurrence and characteristics of solar energetic particle (SEP) events related to full halo coronal mass ejections (FHCMEs) from source locations close to the central meridian of the Sun. Halo CMEs detected by SOHO/LASCO between 1996 and end of 2014 originating from source locations between solar longitudes E10 and W10 were first identified. The CMEs were divided in three groups according to the latitude of the source region: 26 equatorial events in the latitude range [N10, S10], 16 northern events in the range (N10,N20], and 22 southern events in the range (S10, S20]. We then searched for associated solar proton events based on SOHO/ERNE observations. In altogether 25 cases (13 equatorial, 6 northern, and 6 southern events) an association was found. For these events, we found good correlations of the peak intensities of 2MeV, 20MeV, and 68MeV protons with both the CME speed and the X-ray flare magnitude, as determined by the soft X-ray peak flux or the event integrated flux. The correlation coefficients ranged from 0.47 to 0.83 for the CME speed, from 0.63 to 0.88 for the X-ray peak flux and from 0.64 to 0.89 for the X-ray integrated flux depending on the proton energy.